Help! I'm trapped in my teacher's body - Strasser, Todd.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1993)
Jake Sherman used to be your average, ordinary twelve year old, until he turned into his weirdo teacher, Mr. Dirksen! To make matters worse, dorky Mr. Dirksen is running around in Jake's body!
"An Apple paperback."
Keywords: Science fiction; Fantasy